Health Communication Strategies and Awareness of Women’s Lifestyle in Aceh - Nelvi Elizarni; Rahmatun Mauliza (Enlightenment Publishing, 2024)
In my research paper, I investigate the critical role of health communication strategies in enhancing awareness of Women’s lifestyle issues in Aceh, Indonesia. I begin by outlining the significant health challenges faced by women in this region, emphasizing the cultural context that influences their lifestyle choices, including nutrition, physical activity, reproductive health, and hygiene. My objective is to analyze existing health communication programs, identify barriers to effective communication, and recommend tailored strategies to improve awareness. Through a comprehensive evaluation of current initiatives, I highlight their effectiveness and cultural sensitivity while addressing obstacles such as socio-economic factors and infrastructure limitations. I propose evidence-based recommendations for culturally relevant and community-driven communication strategies to foster better health outcomes. Ultimately, I argue that targeted health communication is essential for improving Women’s health and well-being in Aceh, with implications for public health policy and practice.